(untitled) (Altre Modernità, 2010)
Contemporary politics stands on an ambiguous relationship with passion. Firstly, passion is, clearly, the very reason of a concern which justifies one’s political involvement and frees himself of a narrow interest, merely waiting, as Olson said, on material advantages. But the capacity of passion to disrupt institutions and to cause the loss of social peace is also self-evident. As a result, representative democracy remains within the limits marked by a reasonable involvement, basing itself on an optimum of indifference (see Braud, 1991). Democracy will therefore prefer citizens scarcely passionate about politics, in order to let the democratic activities or civil celebrations be performed. If the concern with politics is the condition of democratic legitimacy, the excess of involvement disturbs professional politics: passion wouldn’t then be an acceptable attitude if it weren’t regulated by civic self-control.